PENERAPAN MEDIA KARTU KUARTET UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI FAKTA DAN OPINI DI SD - Faiz, Achmad Zaenal; Agus Wardhono; Badri Atul Fikriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students' learning outcomes in understanding factual and opinion sentences through the use of quartet cards in grade V of SDN Sidomulyo 2 Tuban. The method used is Classroom Action Research (CAR) with two cycles involving planning, implementation, observation, and reflection. Data were collected through observation, tests, interviews, and documentation. The results of the study indicate that the application of quartet cards significantly improved student learning outcomes. Classical mastery increased from 19.05% in the pre-cycle stage to 90.48% in cycle II. In addition, teacher and student activities in learning also improved, showing more active and effective involvement. These findings indicate that quartet cards are effective as an alternative in Indonesian language learning for facts and opinions.